1972
DOI: 10.1037/h0032357
|View full text |Cite
|
Sign up to set email alerts
|

Exposure, satiation, and stimulus discriminability.

Abstract: A series of four experiments was carried out in an attempt to understand a curvilinear relationship found between the frequency of stimulus exposure and affective ratings. The inverted-U function was suggestive of satiation effects. Preliminary experiments indicated that stimulus discriminability may work to attenuate the relationship between exposure and affect, but further experiments using a variety of stimuli failed to confirm the initial findings. The possibility was examined that for some stimuli, satiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 19 publications
5
60
0
1
Order By: Relevance
“…In most of the relevant research (Bornstein, 1989;Zajonc, 2001), stimuli are initially neutral with respect to affect before the exposure phase. Interestingly, in one instance in which aesthetically pleasing stimuli (artworks) were presented (Zajonc et al, 1972), satiation effects were similarly robust to the one observed in Experiment 2.…”
Section: Discussionsupporting
confidence: 60%
“…In most of the relevant research (Bornstein, 1989;Zajonc, 2001), stimuli are initially neutral with respect to affect before the exposure phase. Interestingly, in one instance in which aesthetically pleasing stimuli (artworks) were presented (Zajonc et al, 1972), satiation effects were similarly robust to the one observed in Experiment 2.…”
Section: Discussionsupporting
confidence: 60%
“…O delineamento experimental minimalista é o que compara simplesmente a avaliação de estímulos novos com a de estímulos previamente apresentados. Os estudos que realizaram um número elevado de repetições sugerem a possibilidade do efeito se reverter a partir de 10-20 repetições (Stang & O'Connell, 1974;Zajonc, Shaver, Tavris, & Van Kreveld, 1972). No entanto Zajonc, Crandall, Kail, & Swap (1974, Experimento 1) reportam efeitos consistentes até 243 repetições.…”
Section: A(s) Variáve(eis)l Independente(s)unclassified
“…Although exposure effects have been shown for both passive exposure (Zajonc 1968;Zajonc et al 1972;Bornstein 1989) and active exposure where the observer can choose on which object to fixate (Shimojo et al 2003), our hypothesis predicts certain differences between passive and active exposure. Because people have a tendency to look at what they preferösomething we are not explaining here, but something more obviously functionally advantageousöin active (but not passive) exposure scenarios there will be a positive feedback between seeing and preference.…”
mentioning
confidence: 92%
“…Exposure effect (Zajonc 1968;Zajonc et al 1972;Bornstein 1989;Shimojo et al 2003) Cascade effect (Shimojo et al 2003) Enhanced cascade effect for initially similarly-preferred objects (Shimojo et al 2003) (B) The estimated utility of the object, V (X) (B.1) Overexposure to object type X eventually serves as evidence that X is overabundant, inconsistent with it having a high utility, and thereby lowering the estimated utility. The expected utility of acting to obtain X eventually is dampened, and therefore the degree of preference for X should eventually dampen [either counteracting or reversing the initial preference increase in (A.1)].…”
Section: Key Property Of Ourmentioning
confidence: 99%
See 1 more Smart Citation